Chemical and Biological Characterization from Condalia microphylla Fruits, a Native Species of Patagonia Argentina - Boeri, Patricia (2017)
Condalia microphylla Cav. (Rhamnaceae), popularly known as “piquillin”, is widely distributed in Patagonia. The drupes are consumed as fresh fruits by Argentine communities. The aim of this work was to quantify the nutritional value of C. microphylla fruit and the phenolic compounds present and to determine the functional antioxidant properties in vitro and in vivo. The nutritional value was determined according to the Association of Official Analytical Chemists (AOAC) methodology, and phenolic compounds were quantified by diode-array detection (HPLC-DAD). Antioxidant activity in vitro and in vivo was analyzed through the use of the radical species 2,2-diphenyl-1-picrylhydrazyl (DPPH) and zebrafish model, respectively. Quercetin-3-O-rutinoside (rutin) was the single principal phenolic compound. The extracts contained in vitro antioxidant activities and total phenolic contents (TPCs) between 1,143 ± 112 µg and 4,633 ± 174 µg gallic-acid equivalents (GAEs) per 100 g dry weight (DW), though no relationship was found between the latter parameter and the antioxidant activity of the extracts. When zebrafish larvae were exposed to oxidative stress (2.4% v/v H2O2), a concentration as low as 1.44 µg of GAEs/mL of piquillin-derived polyphenols inhibited lipid oxidation by up to 40%. Thus, in view of these advantageous functional food properties and the opportunity to exploit this Patagonian natural resource, piquillin consumption should be promoted worldwide.